Serotype variation among infectious bronchitis viral isolates taken from several areas of Java - Indriani, Risa; ., Darminto (Indonesian Journal of Animal and Veterinary Sciences, 2000)
Infectious bronchitis (IB) is an acute highly contagious viral respiratory disease of poultry caused by virus belongs to the family of Coronaviridae. The virus consist of many serotypes with low level of cross-protectivity among serotypes. Field data showed that the outbreaks of IB were frequently reported in chicken flocks, although vaccinations against the disease have been practiced. Hence, the study on serotype relationship among isolates of the viruses is essentially required. The aim of this study was to isolate and characterize IB viruses from chicken flocks in some areas of Java. Isolation of the virus was carried out in nine-day old embrionated chicken eggs and identified by means of agar gel precipitation (AGP) tests against standard antisera to IB virus. The serotypes of the IB viral isolates were determined by cross-neutralization tests in nine day old embryonated chicken eggs using r value derived from homologous and heterologous serum titres as criteria. This study obtained 12 IB viral isolates which were identified on the basis of the ability to cause lesions in chicken embryos and positive to agar gel presipitation test against standard positive antiserum to the virus. Based on the cross-neutralization tests in embryonated chicken eggs, isolate I.9 was formed to have relationship closed to Mass-41 serotype, while I.2, I. 3, and I.7 isolates were closely to the serotype of Con-46. Virus isolates (I.5, I.14, I.24, and I.25) were decided to have no serotype relationships to either Mass-41 or Con-46 serotype. Since the I.5, I.14, I.24 and I.25 isolates were not neutralized by antisera against the previous identified local infectious bronchitis viral isolates, and that were considered to be distinct serotype to the previously identified local IB viral isolates. Â  Key words: Infectious bronchitis, virus, embryonated egg, cross neutralization test.